Entre delta du Nil et désert, front pionnier agricole et recomposition territoriale en Egypte - Delphine Acloque Desmulier (Carnets de Géographes, 2014)
Desert land reclamation for agricultural expansion has been used as a tool by the different political regimes since the 1950s to solve some of the sharpest problems in Egypt : the proclaimed lack of arable land in a context of fast population growth, the fragmentation of land in the Nile Valley and Delta, unemployment, rural poverty, and even the pollution of the old lands (Mitchell, 1995). Located between the fertile and populated areas of the Nile Delta and the vast areas of arid lands, new lands reclaimed on the desert have experienced a fast expansion of agricultural activities, with the emergence of an agri-capitalist sector, dominated by some large companies since the mid-1980s (Dixon, 2013). However, part of the new reclaimed lands have also been dedicated to the settlement of small-holders through governmental programmes. The purpose of this paper is to study the Western margins of the Nile Delta through the notion of “in-betweenness”. If the new lands are partly shaped by their interactions with the neighbouring territories, they are also characterized by specific internal dynamics, contributing to the emergence of a new agricultural sector and new Egyptian rural territories, as well as highlighting a process of socio-economic differentiation.